Molecular Proof of a Clinical Concept: Expression of Estrogen Alpha-, Beta-Receptors and G Protein-Coupled Estrogen Receptor 1 (GPER) in Histologically Assessed Common Nevi, Dysplastic Nevi and Melanomas - Magdalena Spałkowska (MDPI AG, 2021)
Background and Objectives: Epidemiologic data show significant differences in melanoma incidence and outcomes between sexes. The role of hormonal receptors in the pathogenesis of melanocytic lesions remains unclear, thus we performed this study aiming to assess estrogen receptors expression in different melanocytic lesions. Materials and Methods: We performed a cross-sectional study that included 73 consecutively excised melanocytic lesions. Estrogen receptor alpha (ERα), beta (ERβ), and G-protein coupled estrogen receptor (GPER) expression was analyzed in melanocytes and keratinocytes of common nevi, dysplastic nevi, melanoma, healthy skin margin, and in sebaceous and sweat gland cells. Results: ERβ expression was higher in dysplastic nevi margin melanocytes compared to common nevi (p = 0.046) and in dysplastic nevi keratinocytes compared to melanoma keratinocytes (p = 0.021). ERβ expression was significantly higher in margin melanocytes compared to melanoma melanocytes (p = 0.009). No difference in ERβ expression was shown between melanocytes of three types of lesions. GPER expression was higher in nuclei and cytoplasm of dysplastic nevi (p = 0.02 and p = 0.036 respectively) and at the margin compared to melanoma. GPER expression was lower in sebaceous glands of tissue surrounding common nevi (p = 0.025) compared to dysplastic nevi. GPER expression was higher in skin margin tissue melanocytes (p = 0.016 nuclear, p = 0.029 cytoplasmic) compared to melanoma melanocytes. There were no differences in ERα expression between the melanocytic lesions. Conclusion: Further large-scale studies are warranted to investigate the potential role of ERβ and GPER in the pathogenesis of melanocytic lesions.